2018
DOI: 10.1111/jocn.14237
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of scholarship across eight cohorts of doctor of nursing practice graduates

Abstract: Dissemination of academic scholarly work is an expected outcome for Doctor of Nursing Practice graduates who impact clinical, operational and financial outcomes in complex healthcare delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 17 publications
(26 reference statements)
1
24
1
Order By: Relevance
“…We found that 21% of the projects resulted in publication. This was lower than the 37% in a previous report that included DNP projects from Johns Hopkins University School of Nursing up to 2016 by Becker et al (2018). This may be because these authors, in addition to searching the literature using PubMed and Google Scholar also accepted a print version of a publication provided by the graduate.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We found that 21% of the projects resulted in publication. This was lower than the 37% in a previous report that included DNP projects from Johns Hopkins University School of Nursing up to 2016 by Becker et al (2018). This may be because these authors, in addition to searching the literature using PubMed and Google Scholar also accepted a print version of a publication provided by the graduate.…”
Section: Discussioncontrasting
confidence: 62%
“…The authors noted that the scope and complexity of the projects increased from the first cohort to the fifth cohort and that students in the earlier cohorts were more likely to examine changes in knowledge than students in the later cohorts. In another paper describing publication outcomes of DNP students at Johns Hopkins University School of Nursing, Becker, Johnson, Rucker, and Finnell (2018) described the 156 students enrolled in between 2009–2016 and any publications that they had during their studies and after graduation. Fifty‐eight (37%) students published their DNP Project papers and 20 (13%) published integrative reviews of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study evaluating dissemination requirements found that only 41% require an executive summary to practice site shareholders 8 . Because project requirements and rigor vary, dissemination will correspondingly differ but is essential, shortening gaps in translating evidence into practice at the host site 50 . Organization leaders and mentors are well positioned to ensure that, at a minimum, stakeholders receive a summary of results.…”
Section: Conducting and Disseminating Project Resultsmentioning
confidence: 99%
“…8 Because project requirements and rigor vary, dissemination will correspondingly differ but is essential, shortening gaps in translating evidence into practice at the host site. 50 Organization leaders and mentors are well positioned to ensure that, at a minimum, stakeholders receive a summary of results. See Table 1 for the road map summary.…”
Section: Conducting and Disseminating Project Resultsmentioning
confidence: 99%
“…Another trend documented in natural resources and other disciplines is the expectation for students to publish their research while enrolled in their graduate program rather than after their graduation (Becker, Johnson, Rucker, & Finnell, 2018; Pinheiro, Melkers, & Youtie, 2014). In this study, of the 58 papers published prior to the graduation date of the student, 65% occurred with graduate students completing their degree in the 2000s and 20% with graduates from the 1990s.…”
Section: Discussionmentioning
confidence: 99%